The Influence of Peer Group Education on The Quality of Life of Elderly with Hypertension - Putri Malinda Istifani; Widiharti Widiharti; Ervi Suminar; Diah Jerita Eka Sari (STIKes Patria Husada Blitar, 2024)
Hypertension is a prevalent issue commonly encountered among the aged population, which can significantly impact their overall quality of life. Peer Group Education might be considered as a viable approach to enhancing the overall well-being and quality of life among the aged population. Peer group education refers to the systematic dissemination of education and knowledge to cohorts of individuals who perceive themselves to share commonalities in terms of age, mindset, hobbies, or other relevant attributes with their peers. The objective of this study was to examine the impact of Peer Group Education on the quality of life among elderly individuals diagnosed with hypertension. The research employed a purposive sampling technique, targeting a population of 42 individuals residing in Palebon Duduksampeyan Village. The final sample size consisted of 38 participants. The independent factors were measured using a Standard Operating Procedure (SOP), whereas the dependent variable was assessed by a questionnaire on quality of life. Before peer group education, 36.8% of elderly individuals with hypertension reported a moderately bad quality of life; after peer group education, nearly 81.6% reported a reasonably excellent quality of life. These findings related to the impact of peer group education on the quality of life of elderly people with hypertension. The Wilcoxon ranks test was utilized to assess the impact of peer group education on the quality of life among senior individuals with hypertension. The resultant p-value was 0.008, with a significance level (α) of 0.05. The quality of life of older individuals residing in Palebon Village, Ponkesdes, is impacted by the presence of hypertension.